CTNI-65. INTUITT-NF2, AN ADAPTIVE PLATFORM-BASKET TRIAL FOR NEUROFIBROMATOSIS 2 PATIENTS WITH PROGRESSIVE TUMORS: INTERIM RESULTS OF THE BRIGATINIB TREATMENT ARM. (14th November 2022) - Plotkin, Scott; Allen, Jeffrey; Babovic-Vuksanovic, Dusica; Dinh, Christine; Nghiemphu, Leia; Trippa, Lorenzo; Yohay, Kaleb; Blakeley, Jaishri
Abstract: Neurofibromatosis type 2 (NF2) predisposes affected individuals to vestibular schwannomas (VS), non-vestibular schwannomas (NVS), meningiomas, and ependymomas. We developed an adaptive platform-basket trial to screen multiple drugs against any type of progressive NF2-related tumor. We report the interim analysis of the first treatment arm with brigatinib, an ALK inhibitor that inhibits multiple tyrosine kinases. We conducted a multicenter, phase II, open-label study for subjects ≥12 years old with NF2 and progressive target tumors (baskets: VS, NVS, meningioma, or ependymoma). Up to 5 non-target tumors were followed in each participant. In stage 1, 20 participants (minimum of 2 participants per basket) were treated with brigatinib 180 mg daily. Tumor response was evaluated by MRI every 3 months in year 1 and every 6 months thereafter. Radiographic response (RR) was defined as ≥20% decrease in target tumor volume from baseline. The primary outcome was RR rate. Per protocol, the brigatinib arm would be discontinued if no target tumor achieved a RR at interim analysis. Twenty subjects (median age=25 years, 7 pediatric, 12 females) were treated. Target tumors included 10 VS, 3 NVS, 5 meningiomas, and 2 ependymomas; non-target tumors included 18 VS, 36 NVS, and 14 meningiomas. RR rate for target and non-target tumors was 5% and 22%, respectively. By tumor basket, RR was 28% for meningioma, 26% for non-VS, 4% for VS, and 0% for ependymomas. Annualized tumor growth rates decreased for VS, NVS, and meningioma during treatment. Brigatinib was well tolerated with one dose reduction and one discontinuation due to grade 2 diarrhea. Brigatinib treatment was associated with RR in meningiomas, VS, and NVS. In stage 2, the study will enroll 20 participants in the two most promising baskets (meningioma and NVS). This novel design provides unique ability to assess treatments for hereditary syndromes with multiple primary tumors.